2016
DOI: 10.1177/0271678x16653133
|View full text |Cite
|
Sign up to set email alerts
|

Baseline collateral status and infarct topography in post-ischaemic perilesional hyperperfusion: An arterial spin labelling study

Abstract: Focal hyperperfusion after acute ischaemic stroke could be of prognostic value depending upon its spatial localisation and temporal dynamics. Factors associated with late stage (12-24 h) perilesional hyperperfusion, identified using arterial spin labelling, are poorly defined. A prospective cohort of acute ischaemic stroke patients presenting within 4.5 h of symptom onset were assessed with multi-modal computed tomography acutely and magnetic resonance imaging at 24 AE 8 h. Multivariate logistic regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 55 publications
(93 reference statements)
1
38
0
Order By: Relevance
“…Stroke rehabilitation not only involves neuronal reorganization but also includes vascular remodelling through angiogenesis (Chopp et al ., ). Hyperperfusion in and around the stroke lesions has been described in recent studies (Yu et al ., ; Bhaskar et al ., ), but the evidence about perfusion change in remote GM tissues are rare. Similar to our finding of increased GMV, increased CBF was found in the regions related to cognition (hippocampus) and vision (LG).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke rehabilitation not only involves neuronal reorganization but also includes vascular remodelling through angiogenesis (Chopp et al ., ). Hyperperfusion in and around the stroke lesions has been described in recent studies (Yu et al ., ; Bhaskar et al ., ), but the evidence about perfusion change in remote GM tissues are rare. Similar to our finding of increased GMV, increased CBF was found in the regions related to cognition (hippocampus) and vision (LG).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to structural plasticity, the homeostatic balance in the human brain can be regulated by neurovascular coupling which refers to a cascade of events triggered by an increase in neuronal activity resulting in an increasing of cerebral blood flow (CBF) (Girouard & Iadecola, ). The presence of post‐ischaemic hyperperfusion within or around the stroke lesions has been reported in recent human studies (Yu et al ., ; Bhaskar et al ., ). Our recent study demonstrated that post‐ischaemic hyperperfusion has an association with good outcome after stroke (Yu et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The advent of cutting-edge next generation 320-detector row 640-slice multi-detector CT (MDCT) scanners have facilitated the acquisition of whole-brain, sub-second, and volumetric acquisition of 4D-dCTA data13738. CTP/CTA is not an invasive procedure compared to digital subtraction angiography (DSA), and is routinely obtained during clinical care of stroke patients8323339, has proven to be of added clinical utility in the early evaluation of stroke, facilitating precise localization of site of occlusion40, and identification of hypoperfused territory at risk of infarction41. The CTP was acquired simultaneously with the CTA with the use of same contrast bolus42.…”
Section: Discussionmentioning
confidence: 99%
“…Volumes of the acute perfusion lesion (relative delay time (DT) ≥ 3 seconds) and acute infarct core (relative CBF ≤ 30%) were calculated using previously validated thresholds848. Penumbra volume was defined as the volume of the perfusion lesion (DT threshold ≥ 3 seconds) minus the volume of the infarct core (relative CBF threshold < 30% within the DT ≥ 3 sec lesion).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation